The environmental impacts of bar soap production: uncovering sustainability risks with LCA analysis - Gaurav, Gaur; Dangayach, Govind Sharan; Lal Meena, Makkhan; Chaudhary, Vijay; Gupta, Sumit; Jagtap, Sandeep (MDPI, 2023)
Washing bar soap is widely used and vital in everyday life, especially in developing countries where demand is increasing due to population expansion. However, the production and use of washing bar soap have negative impacts on the environment, and the sustainability of soap packaging is also a concern. This research focuses on measuring the environmental effects of the production phase of washing bar soap while accounting for the differences in soap consumption across brands and consumer behavior during the use phase. The research aims to quantify the ecological burden caused by the production and use of 1 kg of bar soap through a Life Cycle Assessment (LCA) that follows ISO 14040 and 14044 standards. This study also addresses the resource-intensive aspect of soap packaging, particularly plastic packaging, and offers sustainability solutions through circular economy principles. GaBi v8.0 software is used to evaluate various environmental performance indicators, and the results show that eutrophication has the highest burden on the environment compared to other categories. This study highlights the importance of consumer behavior in reducing the environmental impact of washing bar soap, as the use stage of washing bar soap has the most significant impact in most categories.
Keywords: environmental impacts; India; Life Cycle Assessment (LCA); soap manufacturing; sustainability; washing bar soap